Effect of static electric field on ice crystal size reduction during freezing of pork meat - Xanthakis, Epameinondas; Havet, Michel; Chevallier, Sylvie; Abadie, J.; LeBail, Alain (My University, 2013)
The objective of this research was to evaluate the influence of static electric field (SEF) on the freezing of pork meat (pork tenderloin muscle) with respect to the size of ice crystal formulation. The results showed that by increasing the strength of the static electric field, the degree of supercooling was reduced. The measured degree of supercooling varied from 3.93 ± 1.3°C to 1.92 ± 1.45°C for the control and the frozen sample under 12 kV SEF, respectively. Meat microstructure was investigated after Carnoy fixation of the frozen tissues. The overall relative surface of the ice crystals was unchanged. The average equivalent circular diameter of the ice crystals was significantly reduced with increasing SEF; values from 32.79 ± 4.04 μm for the control to 14.55 ± 8.20 μm for the sample frozen at the maximum magnitude electric field which was tested were observed respectively. These findings demonstrate clearly the advantage of freezing under SEF which appears as a promising and innovative freezing process for food systems. Industrial relevance The reduction of freeze damage exerted to any tissue undergoing freezing remains a challenge. The mechanical and biochemical stress caused by the ice crystals to the cellular membranes results in irreversible tissue damage. Freezing under static electric field (SEF) has been identified as a possible means to reduce the size of ice crystals during freezing of biological tissues. In the present study SEF was applied during freezing of pork meat. Our results indicate that the size of the formed ice crystals was significantly reduced under SEF freezing leading to a lower damage on the microstructure of meat. This paper describes an innovative freezing process that could be used in order for higher quality frozen products to be produced.
Keywords: Freezing; Microstructure; Pork meat; Electric field